Solve for L
L=\frac{\sqrt{70}}{35}\approx 0.239045722
L=-\frac{\sqrt{70}}{35}\approx -0.239045722
Share
Copied to clipboard
L^{2}\times 35\times 100=400\times 0.5
Multiply both sides by 0.5.
L^{2}\times 3500=400\times 0.5
Multiply 35 and 100 to get 3500.
L^{2}\times 3500=200
Multiply 400 and 0.5 to get 200.
L^{2}=\frac{200}{3500}
Divide both sides by 3500.
L^{2}=\frac{2}{35}
Reduce the fraction \frac{200}{3500} to lowest terms by extracting and canceling out 100.
L=\frac{\sqrt{70}}{35} L=-\frac{\sqrt{70}}{35}
Take the square root of both sides of the equation.
L^{2}\times 35\times 100=400\times 0.5
Multiply both sides by 0.5.
L^{2}\times 3500=400\times 0.5
Multiply 35 and 100 to get 3500.
L^{2}\times 3500=200
Multiply 400 and 0.5 to get 200.
L^{2}\times 3500-200=0
Subtract 200 from both sides.
3500L^{2}-200=0
Quadratic equations like this one, with an x^{2} term but no x term, can still be solved using the quadratic formula, \frac{-b±\sqrt{b^{2}-4ac}}{2a}, once they are put in standard form: ax^{2}+bx+c=0.
L=\frac{0±\sqrt{0^{2}-4\times 3500\left(-200\right)}}{2\times 3500}
This equation is in standard form: ax^{2}+bx+c=0. Substitute 3500 for a, 0 for b, and -200 for c in the quadratic formula, \frac{-b±\sqrt{b^{2}-4ac}}{2a}.
L=\frac{0±\sqrt{-4\times 3500\left(-200\right)}}{2\times 3500}
Square 0.
L=\frac{0±\sqrt{-14000\left(-200\right)}}{2\times 3500}
Multiply -4 times 3500.
L=\frac{0±\sqrt{2800000}}{2\times 3500}
Multiply -14000 times -200.
L=\frac{0±200\sqrt{70}}{2\times 3500}
Take the square root of 2800000.
L=\frac{0±200\sqrt{70}}{7000}
Multiply 2 times 3500.
L=\frac{\sqrt{70}}{35}
Now solve the equation L=\frac{0±200\sqrt{70}}{7000} when ± is plus.
L=-\frac{\sqrt{70}}{35}
Now solve the equation L=\frac{0±200\sqrt{70}}{7000} when ± is minus.
L=\frac{\sqrt{70}}{35} L=-\frac{\sqrt{70}}{35}
The equation is now solved.
Examples
Quadratic equation
{ x } ^ { 2 } - 4 x - 5 = 0
Trigonometry
4 \sin \theta \cos \theta = 2 \sin \theta
Linear equation
y = 3x + 4
Arithmetic
699 * 533
Matrix
\left[ \begin{array} { l l } { 2 } & { 3 } \\ { 5 } & { 4 } \end{array} \right] \left[ \begin{array} { l l l } { 2 } & { 0 } & { 3 } \\ { -1 } & { 1 } & { 5 } \end{array} \right]
Simultaneous equation
\left. \begin{cases} { 8x+2y = 46 } \\ { 7x+3y = 47 } \end{cases} \right.
Differentiation
\frac { d } { d x } \frac { ( 3 x ^ { 2 } - 2 ) } { ( x - 5 ) }
Integration
\int _ { 0 } ^ { 1 } x e ^ { - x ^ { 2 } } d x
Limits
\lim _{x \rightarrow-3} \frac{x^{2}-9}{x^{2}+2 x-3}